Chiral aspects of hadron structure - Thomas, A. W.; Krein, G. (Elsevier B.V., 2000)
Chiral loop corrections for hadronic properties are considered in a constituent quark model. It is emphasized that the correct implementation of such corrections requires a sum over intermediate hadronic states. The leading non-analytic corrections are very important for baryon magnetic moments and explain the failure of the sum rule (mu(Sigma+) + 2 mu(Sigma-))/mu(A) = -1 predicted by the constituent quark model. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: chiral symmetry; quark model; potential models; hadron spectrum; magnetic moments